How to manage tropical forests more sustainably: The case of Indonesia - Rainer Thiele (Intereconomics, 1994)
Although there is a rationale for a more conservative management of the remaining tropical forests, policy-makers in the tropical countries tend to be reluctant to implement appropriate policy measures, because they fear the short-run economic costs of environmental protection. Taking Indonesia as an example, the following article outlines how it is possible to protect tropical forests more effectively without necessarily foregoing economic gains.
Keywords: 330; Forstpolitik; Umweltpolitik; Nachhaltige Entwicklung; Indonesien; Tropen